(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The coccidologist community recognizes the very significant contributions made by Dr. Evelyna M. Danzig during her 42 year career as a research scientist with the Zoological Institute, Russian Academy of Sciences (and her career continues). She has authored more than 120 scientific papers and books on the systematics of scale insects and whiteflies and has studied the faunas of Central Asia, Caucasus, Siberia, the Far-Eastern Russia, northern Russia, Mongolia, Afghanistan, and Vietnam, to name a few. She has been a mentor for many students of scale-insect systematics, and has written articles on faunistics, life history, polymorphism, phylogeny, identification, classification, and nomenclature. She is an avid collector and has spent many summers observing scale insects in the field as well as mounted on microscope slides. Within the pit scales, soft scales, felt scales, margarodids, armoured scales, and mealybugs, she has characterized 10 new genera and 129 new species. It is a privilege to honor such a productive and knowledgeable colleague.